Hyponatremia and MAP‐kinase inhibitors in malignant melanoma: Frequency, pathophysiological aspects and clinical consequences. (22nd November 2018) - Assan, Florence; Vilaine, Eve; Wagner, Sandra; Longvert, Christine; Saiag, Philippe; Seidowsky, Alexandre; Bourgault‐Villada, Isabelle; Massy, Ziad A.
Abstract: The incidence of malignant melanoma has increased over the past two decades. A combined BRAF/MEK inhibitor regimen has been shown to lead to prolonged survival and progression‐free survival in patients with metastatic BRAF V600‐mutant melanoma. Different nephrotoxic effects have been described, among them hyponatremia. The goal of the present narrative review was to understand the pathophysiological mechanisms driving hyponatremia when using selective BRAF inhibitors and/or MEK inhibitors in order to propose potential strategies to prevent or to treat this side effect. Several mechanisms of kidney injury have been suggested including changes in glomerular and tubular function. However, the precise mechanisms of hyponatremia remain unknown. Our hypothesis is that BRAF/MEK inhibitors lead to hyponatremia and water retention (so‐called dilution hyponatremia) by activating aquaporin 2 (AQP2) trafficking from its intracellular compartment to the luminal cell membrane, and by activating ENaC channel. Therefore, we recommend treating the hyponatremia related to BRAF/MEK inhibitors with restriction of fluid intake.